2019
DOI: 10.1021/acs.iecr.9b04960
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Ozone Decomposition and Peroxone Oxidation of Toluene in an Aqueous Phase Using ab Initio Calculations

Abstract: The application of ozone along with hydrogen peroxide, commonly referred to as peroxone oxidation, is a widely investigated technique for wastewater treatment. Degradation of ozone in water is a key step in the pollutant degradation mechanism, particularly in peroxone oxidation. However, the degradation of ozone in water is not understood at a low pH (<6). This study reveals that current ozone degradation models overestimate degradation at a low pH because the rate constants involved in the dissociation equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Upon simultaneous radicals' formation, when the ROS number is higher than the pollutant number, the ROS will react with others through a terminating pathway to generate secondary ROS (with low reduction potential) and hydrogen peroxide (H 2 O 2 ). Those secondary ROS then predicted it would dominate the oxidation process rather than the primary radicals (Esfahani et al, 2019), while H 2 O 2 will contribute to reducing pH value, as seen in Figure 9.…”
Section: Figurementioning
confidence: 98%
“…Upon simultaneous radicals' formation, when the ROS number is higher than the pollutant number, the ROS will react with others through a terminating pathway to generate secondary ROS (with low reduction potential) and hydrogen peroxide (H 2 O 2 ). Those secondary ROS then predicted it would dominate the oxidation process rather than the primary radicals (Esfahani et al, 2019), while H 2 O 2 will contribute to reducing pH value, as seen in Figure 9.…”
Section: Figurementioning
confidence: 98%
“…Medical researchers have demonstrated that the using and accessing of human to O 3 molecules in high time can make the respiratory burning [4]. The O 3 molecules can make the bust pain, in ammation, tissue devastation, reducing the lung ability, reducing the smell sense and cardiovascular matters [5].…”
Section: Introductionmentioning
confidence: 99%
“…Organic residues are hazardous, non‐biodegradable in the ecosystem, which can constantly accumulate and migrate in the soil, atmosphere, and water resources. [ 2 ] There are many ways including chemical coagulation, ozone oxidation, photocatalytic degradation and adsorption [ 3–6 ] to remove organic pollutants from contaminated water. Among them, adsorption is the currently advocated technique for organic pollutants from wastewater in terms of high efficiency and excellent applicability.…”
Section: Introductionmentioning
confidence: 99%
“…
There are many ways including chemical coagulation, ozone oxidation, photocatalytic degradation and adsorption [3][4][5][6] to remove organic pollutants from contaminated water. Among them, adsorption is the currently advocated technique for organic pollutants from wastewater in terms of high efficiency and excellent applicability.
…”
mentioning
confidence: 99%